2013
DOI: 10.1111/myc.12126
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of galactomannan optical density indices and culture results in bronchoscopic specimens obtained from neutropenic and non‐neutropenic patients

Abstract: Aspergillus infections are major causes of morbidity and mortality among immunocompromised patients. This study was designed to investigate the galactomannan assay optical density (OD) indices relative to the culture results in bronchoscopic samples obtained from neutropenic and non-neutropenic patients. Galactomannan OD indices from 1427 samples from 2005 to 2012, which were sent from 839 patients and were composed of bronchial lavage (BL = 727) and bronchoalveolar lavage fluids (BAL = 700), were retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
(63 reference statements)
1
8
0
1
Order By: Relevance
“…Acquired resistance during clinical course wasn't seen. The coexistence of resistant and susceptible strains in most of the patients, is consistent with the literature and supports current knowledge concerning the probability of coexistence with both resistant and susceptible strains in a patient [15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 88%
See 1 more Smart Citation
“…Acquired resistance during clinical course wasn't seen. The coexistence of resistant and susceptible strains in most of the patients, is consistent with the literature and supports current knowledge concerning the probability of coexistence with both resistant and susceptible strains in a patient [15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 88%
“…The clinical signs and symptoms, computerized tomography findings (cavite-consolidation, multiple nodule, halo) and serum and/or bronchoalveolar lavage galactomannan (GM indices>0,5 for serum in two consecutive specimens; GM indices>1 for BAL specimens) positivity were evaluated in order to decide the clinical significance of A. fumigatus growth [25,26].…”
Section: Patients Characteristicsmentioning
confidence: 99%
“…However, it is recommended in meta-analyses that the cutoff index value be taken as 1.5 in patients with hematological malignancies and 1 in mixed patient populations [ 45 , 46 ]. A study comparing culture and GM in BAL fluid samples emphasized that growth might be expected when the optical index is >1, and a correlation with clinical studies was also demonstrated [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the use of antifungal drugs active in molds leads to an apparent decrease in sensitivity, no significant difference could be found related to Aspergillus spp. Furthermore, there is no difference in the sensitivity of BAL GM in patients with or without neutropenia [ 45 , 50 ]. Similar to serum GM testing, the use of semi-synthetic β-lactam antibiotics may lead to false positive results [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Günümüzde antifungal duyarlılık test sonuçlarının yorumlanmasının, türe özgü direnç sınır değerleri ile yapılıyor olması, tür tanımlamasının önemli oluşunun bir diğer nedenidir. Günümüzde mayaların tanımlanmasında en sık uygulanan yöntem-ler; mikroskopi, kültür ve serolojik testlerdir [18][19][20] . Ancak, invazif Candida enfeksiyonunun semptomları özgül olmadığından, uygulanmakta olan geleneksel tanı yöntemlerinin duyarlılık ve özgüllükleri düşüktür ve bu yöntemler hızlı sonuç vermemektedir 21 .…”
Section: Introductionunclassified